2020
DOI: 10.1007/s00011-020-01400-7
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular events of inflammation induced transdifferentiation (EMT) and regeneration (MET) in mesenteric mesothelial cells

Abstract: In this review we summarize the cellular and molecular events of inflammation induced epithelial-to-mesenchymal (EMT) and mesothelial-to-macrophage transition (MET) during regeneration. Since the receptor transmits the environmental stimulus, downregulating or upregulating the process on an epigenetic level, the intracellular localization of receptors (signaling organelles: early endosomes or lysosomal degradation: late endosomes) plays a crucial role in the signaling events regulating inflammation and regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…The basement membrane degraded, the cytoskeleton was remodelled and reorganized [ 27 ]. The volume of the cytoplasm, the number of the cytoplasmic organelles (rough ER, mitochondria, Golgi vesicles) dramatically increased, indicating that the metabolic rate and synthetic activities of these cells highly increased, but autophagy was blocked [ 28 , 29 ]. We have shown that healthy, non-treated mesothelial cells express toll-like receptor 4 (TLR4) as well (our unpublished results), that is responsible to recognize pathogens and participate in the activation of the inflammatory stimulus [ 9 ].…”
Section: Inflammation-induced Epithelial-to-mesenchymal Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basement membrane degraded, the cytoskeleton was remodelled and reorganized [ 27 ]. The volume of the cytoplasm, the number of the cytoplasmic organelles (rough ER, mitochondria, Golgi vesicles) dramatically increased, indicating that the metabolic rate and synthetic activities of these cells highly increased, but autophagy was blocked [ 28 , 29 ]. We have shown that healthy, non-treated mesothelial cells express toll-like receptor 4 (TLR4) as well (our unpublished results), that is responsible to recognize pathogens and participate in the activation of the inflammatory stimulus [ 9 ].…”
Section: Inflammation-induced Epithelial-to-mesenchymal Transitionmentioning
confidence: 99%
“…An increasing number of evidence support that other cells, including epithelial cells, can respond to inflammatory stimuli, and can contribute to chronic inflammation. As it was discussed before mesenteric mesothelial cells are also equipped, or under inflammatory stimuli, can be equipped with all the tools necessary for inflammatory responses [ 28 , 29 , 31 33 ]. Under inflammatory stimuli they undergo transdifferentiation and as a result of this transformation they become able to produce inflammatory cytokines and ROS.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…PMCs play important roles in pathological conditions, such as peritoneal dialysis dysfunction [ 21 ], intra-abdominal adhesions [ 22 ], peritoneal inflammation, peritoneal tumor dissemination [ 23 ], and endometriosis [ 24 ]. PMCs also play key roles in dynamic regulation processes such as peritoneal repair [ 25 ], scarring [ 26 ], the regulation of macrophage migration [ 27 ], and the promotion of coagulation [ 25 , 28 ], including the formation of fibrin and the promotion of fibrinolysis [ 29 , 30 ].…”
Section: Anatomical Physiological and Pathological Features Of Pmcsmentioning
confidence: 99%
“…In the context of chronic (long term peritoneal dialysis) or acute (surgical) peritoneal tissue injury, mesothelial cells have a dynamic role in tissue repair and scarring 91,92 and regulate macrophage emigration from a site of inflammation 90 ; they can promote procoagulant 93,94 , fibrinogenic and fibrinolytic mediators 95 . The repair process is facilitated by the production of an extracellu lar matrix (ECM) of type I, III, and IV collagen, elastin, fibronectin, laminin, and proteoglycans 91,92 . The repair process is modulated via expression of tumour necro sis factor (TNF) 96 , IL1β 97 , epidermal growth factor (EGF) 98 and transforming growth factor β (TGFβ) 99,100 .…”
Section: Peritoneal Injury and Repairmentioning
confidence: 99%
“…Clinically and experimentally, chronic inflammation of the peritoneal surface is observed following repeated and prolonged peritoneal dialysis for renal failure, which, in turn, gives rise to peritoneal fibrosis through the mechanism of epithelial to mesenchymal transi tion (EMT) of the mesothelial cells 102 . The TGFβ and hypoxia inducible factor (HIF) pathways are involved in this process 91,92 and are likely to be central to several diseases of the peritoneum. Specifically, EMT of meso thelial cells has also been suggested to be involved in the pathogenesis of peritoneal metastases 103,104 .…”
Section: Peritoneal Injury and Repairmentioning
confidence: 99%